Pregnancy-related Mortality in the United States, 2006-2010. Issue 4 (December 2015) - Creanga, A. A.; Berg, C. J.; Syverson, C.; Seed, K.; Bruce, F.C.; Callaghan, W.M.
Abstract : ( Obstet Gynecol . 2015;125:5–12)